International financial management - Eun, Cheol S.; Resnick, Bruce G. (Boston : McGraw-Hill/Irwin, 2007)
The principal objective of this text is to teach students how to be effective global financial managers. Adopting a modular approach for greater flexibility, the book includes learning aids such as end-of-chapter questions, problems and mini-cases.
Foundations of international financial management -- The foreign exchange market, exchange rate determination, and currency derivates -- Foreign exchange exposure and management -- World financial markets and institutions -- Financial management of the multinational firm.
Includes index.
Includes bibliographical references and index.
Keywords: International finance; International business enterprises -- Finance; Foreign exchange; Financial institutions, International